Old and New Uzbekistan – A comparative essay on the last years of Islam Karimov’s reign and Shavkat Mirziyoyev’s presidency - Pachucki-Włosek, Krystian (Eastern Review, 2019)
The article aims to present the positive and negative effects of the change in the position of the President of the Republic of Uzbekistan. The article focuses on economic issues, comparing the policy of President Islam Karimov and the policy of President Shavkat Mirziyoyev. The work also compares the foreign policy of both leaders towards Uzbekistan’s largest political partners: Russia and China. The above article tries to answer the question: are the changes in Uzbekistan significant after 2016 or only superficial?